Developing Supply Chain Management and Lean Environment for Improving the Company Performance - Svetlana A. Kucheryavenko; Svetlana A. Gayvoronskaya; Dmitry A. Popov; Irina V. Chistnikova (International Journal of Supply Chain Management, 2019)
Abstract- The article discusses the ways to improve the efficiency of enterprises and organizations in a constantly changing and competitive environment. They analyzed the approaches to the definition of